Hydroxypropylmethyl cellulose as a primary viscosifying agent in cement slurry at high temperature - Abbas, G. (Universiti Malaysia Pahang, 2013)
The use of polymer in cement slurry is necessary to retain viscosity at ambient temperature and thermal thickening properties with increasing temperature. Current polymers, polysaccharides and their derivatives are extensively studied. At high temperature these polymers do not yield thickening of viscosity, but exhibit loss of slurry and gas migration. Therefore, this study presents hydroxypropylmethylcellulose (HPMC) polymer as a viscosifying agent in cement slurry. The HPMC possesses a strong thermal thickening and solid suspension ability which means low viscosity at ambient temperature and viscosity increase with respect to temperature. Thus, a series of experiments was conducted on HPMC polymer as a viscosifying agent in cement slurry. Different concentrated solutions were prepared (i.e. 1.5 to 2.5 wt), in order to characterize their viscosity with respect to shear rate and increasing temperature up to 100°C. Then, cement slurries were prepared with HPMC as the primary viscosifier, to determine the rheological properties at high temperatures. It was observed that HPMC polymer has increased viscosity from 90°C to 100°C. The improved rheology of cement slurry, in terms of plastic viscosity and yield point at different concentrations, revealed HPMC as a capable viscosifying agent at high temperature. Moreover, increased gel strength with increasing concentration was also observed, which may cause a higher pumping rate on the surface. It was concluded that HPMC polymer acts as a viscosifying agent at high temperature. HPMC-based slurries showed high rheology (plastic viscosity and yield point) with HPMC polymer. Thus, the use of this additional additive should be considered in the design of appropriate cement slurry. © Universiti Malaysia Pahang.